Need for Cognitive Closure in Patients with Social Phobia - A.V. Didenko; O.K. Alenina; A.V. Oglezneva (Клиническая и специальная психология, 2022)
A comparative study of the relationship between the need for cognitive closure, social anxiety, and cognitive strategies for regulating emotions in social phobia was carried out. We examined 135 people (57.8% female; Mage=32.8±11.3 years) with a diagnosis of "Social phobia" (F40.1, ICD-10), combined with other mental disorders (mean disorder duration — 13.1±8.1 years). The comparison group was represented by 100 people without mental disorders (53% female; Mage=35.2±6.5 years). Tools used: Need for Closure Scale by A. Kruglanski and D. Webster adapted by M.I. Yasin; Cognitive Emotional Regulation Questionnaire by N. Garnefski et al., adapted by E.I. Rasskazova et al.; Liebowitz Social Anxiety Scale in the adaptation of I.V. Grigorieva and S.N. Enikolopov. It has been established that the clinical manifestations of social phobia are characterized by a high need for cognitive closure and the used dysfunctional cognitive strategies for regulating the emotional sphere are reflected in the inability to achieve cognitive closure, the impossibility of reducing the level of social anxiety, which increases the motivation for social avoidance.